2007
DOI: 10.1139/v07-038
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the reactions of copper chlorides with OP(NH-t-Bu)3 — Formation of the novel [Cu5Cl10]5– anion via in situ templation

Abstract: X-ray structural investigations have shown that the products of the reaction of CuCl 2 ·2H 2 O and OP [NH-t-Bu] 3 are markedly dependent on solvent and temperature. The polymeric ionic complex [(t-BuNH 3 ) 2 (Cu 3 (OH)(H 2 O)Cl 7 )] ∞ (1), containing a trinuclear anionic repeating unit, is obtained from toluene at 80°C, whereas the 2:1 adduct Cu(t-BuNH 2 ) 2 Cl 2 (4) is formed at 150°C. By contrast, a neutral tetranuclear cluster Cu 4 [PO(NH-t-Bu) 3 ] 4 (µ 4 -O)Cl 6 (2) or the one-dimensional chain [Cu(Py) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…The P atoms in the PTA ligands adopt a slightly distorted tetrahedral environment and the Cu-O-P angle is a little under 140 . These geometric parameters are consistent with those in related structures: Fu & Chivers, 2007) and [CuCl 2 (NHC 4 H 8 O){(O)P(NMe 2 ) 3 } (YIBZEP; Xie et al, 2007).…”
Section: Figuresupporting
confidence: 87%
“…The P atoms in the PTA ligands adopt a slightly distorted tetrahedral environment and the Cu-O-P angle is a little under 140 . These geometric parameters are consistent with those in related structures: Fu & Chivers, 2007) and [CuCl 2 (NHC 4 H 8 O){(O)P(NMe 2 ) 3 } (YIBZEP; Xie et al, 2007).…”
Section: Figuresupporting
confidence: 87%
“…Other nonbridging ligands may be attached to copper(II), such as halides (Jackson et al, 1996;Belford et al, 1972;Fu & Chivers, 2007;Harlow Simonsen, 1977), oxygen-bonded ligands (Churchill & Rotella, 1979;Bertrand & Kelley, 1966), nicotine (Haendler, 1990), oxoamines (Weinberger et al, 1998), pyridine (Nä ther & Jess, 2002;Gill & Sterns, 1970;Duncan et al, 1996;Kilbourn & Dunitz, 1967), imidazole (Zhang et al, 2003;Norman et al, 1989;Erdonmez et al, 1990;Clegg et al, 1988;Corté s et al, 2006), pyrazole (Keij et al, 1991;Liu et al, 2003), triazole (Skorda et al, 2005), tetrazole (Lyakhov et al, 2004), azaindole (Poitras & Beauchamp, 1992), phosphine (Bertrand, 1967), thiazole (Bolos & Christidis, 2002), sulfimide (Kelly et al, 1999), phosphite (Churchill et al, 1975) or sulfoxide (Brownstein et al, 1989;Guy et al, 1988).…”
Section: Commentmentioning
confidence: 99%
“…The preparation and structural characterization of imido analogues of common phosphorus oxoanions is an active area of main group chemistry [1][2][3][4] . Chivers et al 5 found that OP(NHt-Bu) 3 could be protonated and converted to a cation under hydrothermal condition with CuCl 2…”
Section: Introductionmentioning
confidence: 99%
“…Armstrong et al 6 had also investigated the reaction of OP(NHt-Bu) 3 and ZnMe 2 and successfully synthesized some novel zinc cluster compounds exhibited interesting molecular structure. Being motivated these researches, we employed OP(NHt-Bu) 3 , ZnCl 2 and hydrochloric acid as reactor to synthesize novel zinc coordinated compound, but a new organic phosphorous cation compound featured as a supramolecular structure was obtained (Scheme-I). During the past decades, a large number of supramolecular structures have been assembled and characterized due to their interesting structure and many respected applications in sensors, catalysis, optical/optoelectronic and magnetic materials etc.…”
mentioning
confidence: 99%